TEACHING VOCABULARY TO YOUNG LEARNERS USING FLASHCARDS - Firdausah, Amatul; Sari, Dina Merris Maya (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
Teaching vocabulary using flashcards media can help students’ to improve abilities, especially in vocabulary. In this research, the researcher describes the use of flashcards to young learners. Flashcards can help students’ to remember new vocabulary that is still foreign to young learners and make teaching vocabulary with flashcards media to make the learning process more fun and not boring for students’. The study employs qualitative research design. The population in this research involved of this research 11th grade students of MA Islamiyah Candi. 25 students. The instrument used by the researcher was a observation checklist and a rubric score. In the observation checklist that observes teacher and students activities from beginning to end of using flashcard to increase English vocabulary. In collecting the rubric score data by assessing the results of using flashcard to increase English vocabulary the average score that students got is 74,4 . Based on these data we can know from that Teaching Vocabulary To Young Learners Using Flashcards good and students also gave a positive response to this media. The aim is to describe the application of flashcards media to students and to describe the result of Teaching Vocabulary To Young Learners Using Flashcards.